1996
DOI: 10.1021/ie950328e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Extraction of Proteins into Tween 85 Nonionic Microemulsions

Abstract: Protein extraction into Tween 85 nonionic microemulsions is characterized. Apparently, a weak electrostatic interaction is the underlying extraction mechanism. The extraction of several proteins is examined as a function of protein size and net charge. The proteins that extracted successfully are positively charged. A size-exclusion limit (60 kDa) is also evident in these extractions. Tween 85 and several other nonionic surfactants possess a net negative charge at neutral pH. Titration measurements are an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The result is in agreement with the effect of pH on lysozyme adsorption to CB-modified membranes [29]. In addition, previous publications have reported that non-ionic surfactants such as Tween 85, Span 20 and Span 60 are negatively charged at neutral pH [12,30], so weak electrostatic attractions between Span 85 and lysozyme (isoelectric point, pI = 11.1) might contribute somewhat to lysozyme extraction at the neutral pH range. In contrast, the extraction yield of ovalbumin decreased from 49% to 36% with increasing pH value.…”
Section: Extraction Behavior Via the Cb-span 85 Reversed Micellessupporting
confidence: 88%
“…The result is in agreement with the effect of pH on lysozyme adsorption to CB-modified membranes [29]. In addition, previous publications have reported that non-ionic surfactants such as Tween 85, Span 20 and Span 60 are negatively charged at neutral pH [12,30], so weak electrostatic attractions between Span 85 and lysozyme (isoelectric point, pI = 11.1) might contribute somewhat to lysozyme extraction at the neutral pH range. In contrast, the extraction yield of ovalbumin decreased from 49% to 36% with increasing pH value.…”
Section: Extraction Behavior Via the Cb-span 85 Reversed Micellessupporting
confidence: 88%
“…This step is associated with the recovery of the membrane phase. Some of the ELM's applications include separation of sugars, 15 organic acids, 16,17 amino acids, 18-21 proteins 22 and antibiotics.…”
Section: -14mentioning
confidence: 99%
“…This step is associated with the recovery of the membrane phase. ELM applications include separation of sugars (Ikeda et al 2003), organic acids (Yordanov and Boyadzhiev, 2007;Demirci et al, 2003), amino acids (Kaghazchia et al, 2006;Mohagheghi et al, 2008;Oshima et al, 2003;Bayraktar, 2001), proteins (Vasudevan and Wiencek, 1996) and antibiotics (Habaki et al, 2008;Lee, 2002).…”
Section: Introductionmentioning
confidence: 99%